(untitled) (Al-Academy, 2020)
This research deals with the fact that arts exit from their familiar context in practice and enter in the context of the fantasy and exoticism picture. In order to understand the theatrical phenomenon and know the way of its production of the fantasy picture, especially the acting performance in its transitions between the real and fantasy. This study consists of: an introduction of the research in which the researcher presented the research problem, importance and objectives. The theoretical framework dealt with founding a theoretical part for the research consisting of two sections: the first (fantasy: the concept and the working) and the second (techniques of acting performance in the fantasy theatrical directions). The two researchers came up with a set of indicators that have been used in analyzing the research sample which has been limited to the acting performance of the theater show (damned hour). The two researchers, after the analysis, came up with a set of results including: the movement technique in the actor’s performance does not require the tranditional and familiar rules in the traditional theatre, rather the movement is associated with the fantasy picture